As informações que dão suporte ao processo decisório e a influência dos grupos que as processam - Max Cirino de Mattos (1998)
In a competitive environment, organizations must react to external inputs dynamically, and the impact of their decisions may influence their position in the market. Organizational decisions are fundamental for their survival, and effective information management is a competitive advantage when it offers an appropriate decision support. Structuring the flow and the content of the organizations internal information in accordance with a fast and secure information system is a basic step to identify the internal strengths and weaknesses. Diverse interpretations of the same information evolve as a result of the characteristics of individuals and groups. When that happens it can introduce ambiguity or equivocality in the decision process. Based on the analysis of documents and on data collected through interviews and focused observations in a telecommunication firm, this study investigated information flows in the making of a monthly performance report. All the users of this report are members of top management. Based on the analysis of these information flows we concluded that the groups interpretations the social representations about the information that support their decision process can influence the firms performance. This happens as a result of the lack of structure in the transmission of information and consense about critical concepts. Some formal guidelines that may orient the organizational efforts towards the improvement of information flows are suggested. The assignment of roles concerning the management of access to information within the company. We also recommended that understanding the creation of social representations within the company may lead to an effective implementation of these guidelines. In addition, it would make it possible to identify potential needs of organizational dissemination of knowledge throughout the company.